2019
DOI: 10.1186/s12866-019-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

AcrAB-TolC efflux pump system plays a role in carbapenem non-susceptibility in Escherichia coli

Abstract: Background Efflux pump mediated antibiotic resistance is an unnoticed and undetected mechanism in clinical microbiology laboratory. RND efflux systems are known for aminoglycoside and tetracycline resistance whereas their role in carbapenem non-susceptibility is not established. The study was undertaken to investigate the role of efflux pump in providing resistance against carbapenems and their response against concentration gradient carbapenem stress on the transcriptional level of the AcrAB gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…S2 in the supplemental material), which may be due to induction of efflux pump expression in the WT strain in the presence of chloramphenicol. Prior studies have shown that the presence of stress can increase pump expression by 4-fold ( 40 , 43 ), which is comparable to the impact of deleting acrR ( 40 – 42 ). We found that treatment with high concentrations of chloramphenicol repressed bacterial growth for multiple days.…”
Section: Resultsmentioning
confidence: 87%
“…S2 in the supplemental material), which may be due to induction of efflux pump expression in the WT strain in the presence of chloramphenicol. Prior studies have shown that the presence of stress can increase pump expression by 4-fold ( 40 , 43 ), which is comparable to the impact of deleting acrR ( 40 – 42 ). We found that treatment with high concentrations of chloramphenicol repressed bacterial growth for multiple days.…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, E36 was one of the few isolates resistant to the carbapenem antibiotics, imipenem and meropenem, ( Table 1 and S1), and yet we did not detect any obvious carbapenem resistance genes in its genome. As carbapenem resistance can be due to a variety of mechanisms [ 90 , 91 ], it is possible that we failed to detect such genes due to the draft nature of our genome assemblies. Further studies will be required to determine the mechanism of carbapenem resistance in this strain.…”
Section: Discussionmentioning
confidence: 99%
“…As per a study done by Chetri et al, 2019 a strong association between ertapenem resistance and AcrA over-expression was observed which has not been noticed earlier. Also, the over-expression of AcrB towards imipenem stress was noticed in this study is unique of its own [14]. AcrD, a transporter protein which belongs to RND superfamily of efflux pump was found to be associated with aminoglycosides resistance [15] did not show any role in carbapenem resistance in the above study [14].…”
Section: Introductionmentioning
confidence: 83%